ENGINEERING METHOD OF MODELING AND OPTIMIZATION OF CHEMICAL-TECHNOLOGICAL PROCESSES - I. V. Veselov; Y. A. Gamlitskiy (Российский технологический журнал)
In the proposed work, the engineering method of modeling and optimization will be described using the example of tire development and rubber products. A new kind of objective function is proposed that allows to determine almost completely optimal technological process parameters (including properties of raw materials and raw materials) taking into account the robustness. Examples of application of the proposed method are given.